Punicalagin Targets Atherosclerosis: Gene Expression Profiling of THP-1 Macrophages Treated with Punicalagin and Molecular Docking - Etimad Huwait; Sanaa Almowallad; Rehab Al-Massabi; Salma Saddeek; Kalamegam Gauthaman; Alexandre Prola (Current Issues in Molecular Biology, 2022)
Atherosclerosis is an important cause of cardiovascular disorders worldwide. Natural botanical drugs have attracted attention due to their antioxidant, anti-inflammatory, and antiatherogenic properties in the treatment of atherosclerosis. Punicalagin is the major bioactive component of pomegranate peel, and has been shown to have antioxidant, anti-inflammatory, antiviral, anti proliferation, and anticancer properties. To explore its antiatherogenic properties at a molecular level, we investigated the genome-wide expression changes that occur in differentiated THP1 cells following treatment with a non-toxic dose of punicalagin. We also conducted a molecular docking simulation study to identify the molecular targets of punicalagin.